Detection of intestinal parasites on field-grown strawberries in the Federal District of Brazil - Silva, Sandra Regina Morais da (2014)
Introduction This study evaluated the presence of pathogenic human parasites on field-grown strawberries in the Federal District of Brazil. Methods A total of 48 samples of strawberries and 48 soil samples from 16 properties were analyzed. Results Contaminated strawberries were detected in 56% of the properties. Schistosoma mansoni, Ascaris lumbricoides or Ascaris suum, Balantidium coli, Endolimax nana, and Entamoeba spp. were detected. Soil was contaminated with Entamoeba spp., Entamoeba coli, Strongyloides spp., Ancylostomatidae, and Hymenolepis nana. Conclusions Producers should be instructed on the safe handling of strawberries in order to reduce the incidence of strawberries that are contaminated with enteroparasites.